Correlation between β-HCG and Doppler in post molar surveillance - S., Priyadarsini; A., Gigi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Gestational trophoblastic disease encompass a spectrum of neoplastic disorders that arise from placental trophoblastic tissue after abnormal fertilisation. Most molar pregnancies spontaneously resolve after uterine evacuation with no further sequelae. However, at any time during or after gestation malignant transformation may occur in approximately 10% to 20% of molar pregnancies. Quantification of βHCG is considered as the ideal method of post molar surveillance. The regression of the disease could be reliably assessed by observing the changes in low resistance flow which paralleled the gradual decrements in serial βHCG levels. To correlate uterine artery blood flow characteristics to serum βHCG levels in the follow up of patients with gestational trophoblastic disease after molar evacuation. Methods: 50 patients with gestational trophoblastic disease after evacuation were followed up by serum βHCG titres and Doppler ultrasonography of uterine arteries. The relationship between the Doppler indices and the serum βHCG titres were evaluated by paired –t test and Pearsons correlation analysis. Results: Significant negative correlations were observed between Systolic/Diastolic (S/D) ratios, Resistance Indices(RI) and Pulsatility indices (PI) and the absolute values of serum βHCG levels, with correlation coefficients of -0.5, -0.46 and -0.40 (p<0.01). The mean values of βHCG showed a decreasing trend from 1st week to 4th week. The mean value of RI, PI and S/D Ratio showed an increasing trend from 1st week to 4th week. However, the difference in mean values of βHCG and Doppler indices at 1st week and 4th week were analysed by paired t test and found to be statistically insignificant(p>0.05) in patients with spontaneous remission. Conclusion: Uterine artery Doppler indices can be used as an adjunct to βHCG for the surveillance of patients with gestational trophoblastic disease after molar evacuation to predict remission of the disease.